Habitat Association Predicts Genetic Diversity and Population Divergence in Amazonian Birds - Harvey, Michael G. Harvey Michael G. (Museu Paraense Emilio Goeldi, 2018)
The ecological traits of organisms may predict their genetic diversity and population genetic structure and mediate the action of evolutionary processes important for speciation and adaptation. Making these ecological-evolutionary links is difficult because it requires comparable genetic estimates from many species with differing ecologies. In Amazonian birds, habitat association is an importante component of ecological diversity. Here, we examine the link between habitat association and genetic parameters using 20 pairs of closely related Amazonian bird species in which one member of the pair occurs primarily in forest edge and floodplains and the other occurs in upland forest interior. We use standardized geographic sampling and data from 2,416 genomic markers to estimate genetic diversity, population genetic structure, and statistics reflecting demographic and evolutionary processes. We find that species of upland forest have greater genetic diversity and divergence across the landscape as well as signatures of older histories and less gene flow than floodplain species. Our results reveal that species ecology in the form of habitat association is an important predictor of genetic diversity and population divergence and suggest that differences in diversity between floodplain and upland avifaunas in the Amazon may be driven by differences in the demographic and evolutionary processes at work in the two habitats.